KULDESAK STUDI KEWARGANEGARAAN - Al-Rasyid, Machmud (PKn Progresif, 2006)
Civics is one study of political science. As long long ago it was adapted from law program in PTPG in Indonesia. The exposure of juridical program is so dominant that needs adoption political science approach in civics studies. As the civics program is demanded to produce teachers at school, that material not only civics but also learning method is really needed to form crative, innovative, and responsible pedagogue cempentence